2004
DOI: 10.1073/pnas.0308725100
|View full text |Cite
|
Sign up to set email alerts
|

Sister grouping of chimpanzees and humans as revealed by genome-wide phylogenetic analysis of brain gene expression profiles

Abstract: Gene expression profiles from the anterior cingulate cortex (ACC) of human, chimpanzee, gorilla, and macaque samples provide clues about genetic regulatory changes in human and other catarrhine primate brains. The ACC, a cerebral neocortical region, has humanspecific histological features. Physiologically, an individual's ACC displays increased activity during that individual's performance of cognitive tasks. Of Ϸ45,000 probe sets on microarray chips representing transcripts of all or most human genes, Ϸ16,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
1
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(171 citation statements)
references
References 48 publications
8
159
1
3
Order By: Relevance
“…An alternate, albeit related, explanation would be that regions with low genetic variance have greater functional constraints on their determinants of cortical thickness, such that genetic mutations influencing these regions will typically be eliminated quickly from the population through purifying selection. Comparative genomic experiments have shown that a subset of neurally-expressed genes have evolved more rapidly in humans than in other primates [Chimpanzee Sequencing and Analysis Consortium, 2005;Dorus et al, 2004;Khaitovich et al, 2005]; both gene expression changes and protein sequence modification have accelerated in humans relative to nonhuman primates [Caceres et al, 2003;Enard et al, 2002;Gu and Gu, 2003;Hsieh et al, 2003;Uddin et al, 2004]. The findings of increased genetic variance in evolutionarily recent structures may represent a remnant of these rapid neurogenetic changes that accompanied our divergence from other primates.…”
Section: Discussionmentioning
confidence: 99%
“…An alternate, albeit related, explanation would be that regions with low genetic variance have greater functional constraints on their determinants of cortical thickness, such that genetic mutations influencing these regions will typically be eliminated quickly from the population through purifying selection. Comparative genomic experiments have shown that a subset of neurally-expressed genes have evolved more rapidly in humans than in other primates [Chimpanzee Sequencing and Analysis Consortium, 2005;Dorus et al, 2004;Khaitovich et al, 2005]; both gene expression changes and protein sequence modification have accelerated in humans relative to nonhuman primates [Caceres et al, 2003;Enard et al, 2002;Gu and Gu, 2003;Hsieh et al, 2003;Uddin et al, 2004]. The findings of increased genetic variance in evolutionarily recent structures may represent a remnant of these rapid neurogenetic changes that accompanied our divergence from other primates.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found a high rate of expression changes in the brain along the human lineage (Enard et al, 2002;Gu and Gu, 2003;Khaitovich et al, 2005a, b), while other studies found little or no evidence of an accelerated rate (Hsieh et al, 2003;Uddin et al, 2004;Gilad et al, 2006a, b). The reasons for these differences may be technical or methodological and have been discussed elsewhere (Gilad et al, 2006a, b).…”
Section: Comparative Datamentioning
confidence: 99%
“…For example, the differential expression of genes related to aerobic energy metabolism has only been found in studies examining expression in brain regions between species [67,69,91]. To get a more complete picture of the important functional shifts in gene expression between tissues and species, future studies will need to examine more tissues throughout the body.…”
Section: Evidence From the Evolution Of Gene Expression Between Humanmentioning
confidence: 99%
“…(b) Evidence for changes in energy transport In brain tissues, there is a consistent pattern of changes in expression of genes critical to aerobic energy metabolism [67,69,71,91]. This includes categories such as oxidative phosphorylation, electron transport and other nuclearencoded genes that function in the mitochondria.…”
Section: Evidence From the Evolution Of Gene Expression Between Humanmentioning
confidence: 99%